Prevention of High-Fat Diet-Induced Hypercholesterolemia by Lactobacillus reuteri Fn041 Through Promoting Cholesterol and Bile Salt Excretion and Intestinal Mucosal Barrier Functions - Lu, Mengyao; Sun, Jin; Zhao, Yuning; Zhang, Haowen; Li, Xinyue; Zhou, Jingbo; Dang, Hongyang; Zhang, Jidong; Huang, Wenjing; Qi, Ce; Li, Duo (Frontiers in Nutrition, 2022)
Objectives: Lactobacillus reuteri Fn041 (Fn041) is a probiotic isolated from immunoglobulin A coated microbiota in the human breast milk of Gannan in China with a low incidence of hypercholesterolemia. This study aims to explore the role and mechanism of Fn041 in preventing hypercholesterolemia caused by a high-fat diet in mice. Methods: C57BL/6N mice were fed a low-fat diet or a high-fat diet and gavage with Fn041 and Lactobacillus rhamnosus GG (LGG) for 8 weeks. Results: Both Fn041 and LGG prevented the occurrence of hypercholesterolemia, liver and testicular fat accumulation. In addition, a high-fat diet causes intestinal dysbiosis and mucosal barrier damage, which is associated with hypercholesterolemia. Fn041 prevented the high-fat diet-induced reduction in alpha diversity of intestinal microbiota and intestinal mucosal barrier damage. Fn041 treatment significantly increased fecal total cholesterol and total bile acids. Conclusions: Fn041 prevented hypercholesterolemia by enhancing cholesterol excretion and mucosal barrier function.